Switzerland : Selected Background Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This Selected Background Issues paper on Switzerland reviews a few monetary and exchange rate issues, including questions related to the monetary policy framework and the assessment of recent monetary conditions and exchange rate developments. The paper examines the Swiss savings and investment levels from a welfare point of view, employing for this purpose some 'golden rule' criteria of capital accumulation put forward in the academic literature. It finds that, with its unusually high levels of saving, Switzerland may be one of the few advanced industrialized countries that strictly fulfills the 'golden rule' criteria.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet